A new species of the genus Neatus J. L. Leconte, 1862 (Coleoptera: Tenebrionidae: Tenebrionini) from Türkiye, with new country records and a key to holarctic species - Soldati, Fabien; Leo, Piero; Jansson, Nicklas; Avci, Mustafa; Coşkun, Mustafa; Kayiş, Tamer (Zootaxa, 2025)
Neatus turcicus sp. nov. is described from southern Türkiye, in the provinces of Adana, Isparta, Konya and Mersin. In the provinces of Isparta and Mersin the new species was discovered during the Turkish Oak Habitat Project (TOHP), a large-scale study of old oaks in Türkiye. It is compared with all known Neatus species from the Holarctic Region and is closely related to N. noctivagus (Mulsant & Rey, 1853) and N. subaequalis Reitter, 1920. Material of all Neatus species is studied, including topotypical specimens, with analysis of their geographical distribution, and N. noctivagus is a new country record for Greece and Türkiye. A first key to all Neatus species is proposed, including new morphological characters. Photos of aedeagi of all species are also presented for the first time.